2013
DOI: 10.7734/coseik.2013.26.5.385
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Adaptive Finite Element Mesh Generation for Dynamics

Abstract: The finite element method has become the most widely used method of structural analysis and recently, the method has often been applied to complex dynamic and nonlinear structural analyses problems. Even for these complex problems, where the responses are hard to predict, finite element analyses yield reliable results if appropriate element types and meshes are used. However, the dynamic and nonlinear behaviors of a structure often include large deformations in various portions of the structure and if the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…(8), the representative error of element i is weighted by the element's area with respect to the total area and thus the relative order of errors for all elements are computed to identify elements to be adaptively changed. Previous studies have shown that this is computationally very efficient for achieving this (Yoon, 2012;Yoon, 2013).…”
Section: Error Estimations With Representative Strainsmentioning
confidence: 99%
See 3 more Smart Citations
“…(8), the representative error of element i is weighted by the element's area with respect to the total area and thus the relative order of errors for all elements are computed to identify elements to be adaptively changed. Previous studies have shown that this is computationally very efficient for achieving this (Yoon, 2012;Yoon, 2013).…”
Section: Error Estimations With Representative Strainsmentioning
confidence: 99%
“…(6) is only used to define the error and various attempts are generally devoted to estimating errors that resemble Eq.(6). The error defined below are based on the representative strains of element based on the standard deviations of the strains at the Gauss points in the element computed during the previous finite element analysis (Jeong and Yoon, 2003;Yoon and Park, 2010). The rationale for this is that as solution approaches the exact solution, the strains within an element must approach a constant value and thus the standard deviations must approach zero at the Gauss points.…”
Section: Error Estimations With Representative Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the finite element mesh for these types of analyses must be dynamically adaptive, and considering the rapid process of analysis in real time, the dynamically adaptive finite element mesh generating schemes must be computationally efficient. When the method is applied to dynamics analyzed in the time domain, the meshes may need to be modified at each time step as the finite element results of an analysis largely depend on the mesh and the element types used (Heesom and Mahdjoubi, 2001;Jang and Lee, 2011;Yoon and Park, 2010).…”
Section: Introductionmentioning
confidence: 99%